Bitcoin in the South African market: a safe haven or hedge? - Mhlanga, Fortune Nhlanhla (My University, 2022)
Crypto-currency has been growing rapidly since its inception and this development has led to increasing interest from investment portfolio managers to understand if crypto-currency can be used as a financial asset. One of the major objectives of these managers is to minimize losses and maximize profits on the investments they made. Loss in portfolio value is always possible. Consequently portfolio managers are always searching for new, uncorrelated, asset classes that can be used to hedge their existing positions. This study seeks to understand if Bitcoin can act as a hedge or a safe haven for stocks and bonds in South Africa. The principal regression model is used to probe the weekly, monthly, and quarterly Bitcoin, stocks and bonds historical data from 2012 to 2021. This study shows that Bitcoin can act as a hedge against bonds. Results from weekly and monthly historical data show that Bitcoin can act as a hedge against stocks and a safe haven for stocks and bonds. Quarterly historical data results do not support the latter results.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Bitcoin; Crypto-currency; South African market